Generating Public Sector Resources to Finance Sustainable Development : Revenue and Incentive Effects - Pagiola, Stefano (Washington, DC: World Bank, 2013)
The paper discusses how developing countries can generate some of the resources they need for sustainable development. Developing country government already spend significant amounts of resources on a variety of activities, but the evidence suggests that sometimes, there is substantial scope for them to generate additional resources, and most importantly perhaps, to free substantial amounts of resources which are currently being used inefficiently. The paper attempts at setting the scope on the magnitude of resources that might be generated, or freed by a variety of public sector actions. It begins by examining the potential to reform existing policies which are not only costly, but often unsustainable, and environmentally damaging. Then, it reviews means for generating new financial flows, capturing greater share of rents from natural resources, and instituting "green" levies. Lessons suggest as a potential source of additional revenues, the reform of subsidies, making sub-sectors financially sustainable, reforms which in turn reduce environmental damage, but considering reform policies that would not inadvertently harm the poor. This requires political will, good governance, capacity building, and investment.